2017
DOI: 10.11113/mjfas.v13n4.744
|View full text |Cite
|
Sign up to set email alerts
|

Theoretical investigation of the lattice energy of urea: Insight from DFT using systematic cluster method

Abstract: Lattice energy is the energy needed to form crystals of a compound from the individual molecules. It is related to the stability of a compound in the solid state. In this study, systematic cluster method has been applied to obtain the lattice energy of urea. Using this method, the effect of solid state environment is included in a systematic way. Starting from the small clusters containing a few molecules, the largest cluster we studied contains 84 molecules. In order to improve the results from the cluster me… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
1
1

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(2 citation statements)
references
References 15 publications
0
2
0
Order By: Relevance
“…1, was applied. Previous studies have shown that systematically clustering a structure would lead its energy closer to the experimental values as the structure goes bigger [35]. However, the finite structure still gives out the same interaction potential as infinite structure [34].…”
Section: ■ Introductionmentioning
confidence: 81%
See 1 more Smart Citation
“…1, was applied. Previous studies have shown that systematically clustering a structure would lead its energy closer to the experimental values as the structure goes bigger [35]. However, the finite structure still gives out the same interaction potential as infinite structure [34].…”
Section: ■ Introductionmentioning
confidence: 81%
“…5, four hydroxyls exist in the middle of the kaolinite ring. However, only three hydroxyls had a maximum point which is OH 51-52 , OH 13-14 , and OH [19][20][21][22][23][24][25][26][27][28][29][30][31][32][33][34][35][36] . As mentioned before, OH 20-28 is the hydroxyl that points to the middle of the kaolinite ring.…”
Section: A Quantitative Study Of Kaolinite Electrostatic Surface Pote...mentioning
confidence: 99%